Pentingnya Membangun Rasa Toleransi dan Wawasan Nusantara dalam Bermasyarakat - Gita Bangun Prakoso; Fatma Ulfatun Najicha (Prodi PPkn Universitas Slamet Riyadi, 2022)
Indonesia is a country that have a lot of diversity. Diversity of indonesian separated to race, culture, religions, ethnicity, customs and groups. Diversity in a nation can have advantages and disadvantages. As a member that live on a country that have so many diversity, we can reduce the disadvantages with tolerance and archipelago insight. This literature will discuss about conflict caused by diversity. In this literature we will know that tolerance and archipelago insight can prevent conflict because of diversity.